Economic theory and operations analysis - Baumol, William J. (Englewood Cliffs, N.J. : Prentice-Hall, 1961)
This edition has a few minor changes, most notably an attempt to improve the explanation of the basic theorem of linear programming. A substantial number of exercises have been added, and brief discussions of the applications of differential calculus to standard economic theory have been inserted at the end of Chapters 9, 11, 13 and 14. The book is divided into four parts. Analytic Tools of Optimization; Micro-economic Analysis; Recent Developments in Mathematical Economics; and Postscript on Computers.
Includes bibliographical references and index.
rpm 11/10/2017
Loans
Keywords: Economics; Economics, Mathematical; Operations research; Mathematical analysis